Towards the digital modelling of natural entities and its Pseudo-representation. (3rd April 2022) - Wang, Cifeng; Zou, Ziming; Hu, Xiaoyan; Li, Yunlong; Bai, Xi
ABSTRACT: With the development of new methods and the tremendous progress in transducer technology, the observations and researches have become more and more stereoscopic and full-scale. In order to build the multi-source data fusion system propping up the computations, such as process evolution prediction, structure discovery and association analysis, the digital modelling of the natural entity needs to be carried out, which would help build the corresponding digital entity. In this study, the concepts and models in geoscience are introduced, and the issues overlooked in the digital modelling theories are discussed. On this basis, a unified conceptual model and its pseudo-representation (BPRModel) are built. Furthermore, the application of the model is illustrated under the research of specific natural entity, that is to say, the Earth's magnetosphere.